Analysis of the Tsunami of December 26, 2004, on the Kerala Coast of India-Part I: Amplitudes - N. P. KURIAN, M. BABA, K. RAJITH, N. NIRUPAMA, AND T. S. MURTY (Marine Geodesy, 29: 265-270, 2006, 2006)
The Indian Ocean tsunami of December 26, 2004, not only affected the Bay of Bengal coast of India but also part of the Arabian Sea coast of India. In particular, the tsunami caused loss of life and heavy damage on some parts of the Kerala coast in southwest India. The tsunami traveled west, south of Sri Lanka, and some of the tsunami energy was diffracted around Sri Lanka and the southern tip of India and moved northward into the Arabian Sea. However, tsunami, being a long gravity wave with a wave length of a few hundred kilometers, has to take a wide turn. In that process, it missed the very southern part of the Kerala coast and did not achieve large amplitudes there. However, further north, the tsunami achieved amplitudes of upto 5 m and caused loss of life and significant damage. Here we identify the physical oceanographic processes that were responsible for selective amplification of the tsunami in certain locations